THE EFFECTIVENESS OF GIVING COFFEE DREGS COMPOST AND POC HORSE URINE ON RADISH PRODUCTION (Raphanus Sativus L.) - Irwangga, Yusrial; Tarigan, Ruth Riah Ate; Luta, Devi Andriani (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
This study aims to determine the effectiveness of using coffee grounds and horse urine POC administration on the production of radish (Raphanus sativus L.). This research method used a factorial randomized block design (RBD) consisting of 2 factors. The factors studied were coffee grounds compost (K) treatment factors consisting of 4 levels K0 = 0 kg/Plot, K1 = 1 kg/Plot, K2 = 2 kg/Plot, K3 = 3 kg/Plot and the second factor was the provision of POC Horse urine (U) consists of 4 levels, namely U0 = 0 ml/liter of water/plot, U1 = 300 ml/liter of water/plot, U2 = 600 ml/liter of water/plot, U3 = 900 ml/liter of water/plot. Parameters observed were tuber length (cm), tuber production per sample (g) and tuber production per plot (g). The results showed that the application of coffee grounds compost and horse urine POC to radish production had a very significant effect on the parameters of tuber length, tuber production weight per sample and tuber production weight per plot. Where the best treatment for coffee grounds compost was in the K3 treatment (3 kg), the best treatment for horse urine POC was in the U3 treatment (900 ml/liter of water/plot).